2019
DOI: 10.1111/wej.12529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flexible vegetation lodging on overland run‐off resistance

Abstract: Vegetation is an important factor in overland runoff. Due to its flexibility, the vegetation will often become lodged, which will change the characteristics of the flow. However, current studies of flow resistance from flexible vegetation are primarily limited to qualitative analyses. To study the quantitative relationship between the resistance coefficient λ and the vegetation lodging angle θ, an indoor simulation experiment was carried out. The results showed that λ gradually decreased with increasing θ unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, aquatic canopies can also provide resistance by raising the local water levels in rivers and reducing the flow velocity. Therefore, investigating the turbulence structure in water bodies under the influence of vegetation canopy can help further the understanding of pollutant and sediment transport (Nepf, 2011;Park and Hwang, 2019;Zhang et al, 2019;Abdolahpour et al, 2020). It can also shed light on the water transport and flooding capacity of the river, which has important implications for ecological restoration projects (Waycott et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aquatic canopies can also provide resistance by raising the local water levels in rivers and reducing the flow velocity. Therefore, investigating the turbulence structure in water bodies under the influence of vegetation canopy can help further the understanding of pollutant and sediment transport (Nepf, 2011;Park and Hwang, 2019;Zhang et al, 2019;Abdolahpour et al, 2020). It can also shed light on the water transport and flooding capacity of the river, which has important implications for ecological restoration projects (Waycott et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The above research shows that the f–Re relation is affected by vegetation types and underlying surface conditions, which indicates that Re is not the only factor to predict the resistance coefficient (Wang et al, 2018). In fact, f is also affected by vegetation coverage (Li et al, 2013; Shang et al, 2020), stem diameter (Zhang et al, 2018; Zhao et al, 2015), slope gradient (Zhang, Liu, et al, 2019), and water depth (Baptist et al, 2010). The above studies indicated that the resistance mechanism of the overland flow is complicated and the controlling factors of all variables involved and the resistance coefficient f need to be studied in depth.…”
Section: Introductionmentioning
confidence: 99%